The Role of Islamic Human Resources anda Innovation in Supporting Business Sustainability of Coastal Communities in Sinjai Regency - Nurwahida, Nurwahida; Ridwan, Hardiyanti; Nabir, Abd. Muhaemin; Subha, Rahman; Lubis, NuruL Fajriani (Economos : Jurnal Ekonomi dan Bisnis, 2025)
This study aims to examine: (1) the role of human resources in supporting the sustainability of community businesses in the coastal areas of Sinjai Regency, and (2) the role of innovation in enhancing the continuity of such businesses in the region. The research method employed is descriptive qualitative, with data collected through observation, interviews, and documentation of business actors in the coastal areas. The findings indicate that human resources play a crucial role in managing and sustaining business operations. Coastal communities have demonstrated adaptability and responsibility in running their businesses while adhering to Islamic principles, such as ensuring product halalness, maintaining honesty in transactions, and preserving the marine and coastal environment. Moreover, they have shown awareness of the importance of capacity building through training and informal learning. In terms of innovation, coastal communities have begun utilizing digital technology to expand the marketing reach of their products. Social media platforms such as Facebook, WhatsApp, and Instagram are actively used for promotion and consumer engagement. This technological adoption enhances the competitiveness of local products and broadens market access, thereby supporting greater business sustainability. These findings affirm that the sustainability of coastal community businesses is significantly influenced by the quality of human resources and their ability to innovate, particularly in responding to technological advancements and market demands.